Sufism, Power Politics, and Reform: Al-Rānīrī’s Opposition to Hamzah al-Fanṣūrī’s Teachings Reconsidered - Abdollah Vakily (Studia Islamika, 1997)
Middle of the seventeenth century witnessed the horror of the Acehnese socio-religious life can not be imagined. These events commonly known as a fatwa banning religious follower of the teachings attributed to great figures Fansuri Hamzah. The books are used as a handle follower Hamzah collected by royal officials, stacked and burned in public. The followers themselves must bear the violence the authorities, because of being chased and forced to 'convert' to no longer follow the belief that later became known as followers of Wujudiyah.DOI: 10.15408/sdi.v4i1.788